1979
DOI: 10.1007/bf01318098
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies on the replication of herpes virus ateles-73 in owl monkey kidney cells

Abstract: The replicative cycle of herpesvirus ateles, strain 73 (HVA-73), was examined in the electron microscope and compared to that of other herpesviruses known to be oncogenic. A relatively slow replicative cycle of HVA-73 in owl monkey kidney (OMK) cells allowed us to distinguish cytoplasmic and nuclear stages of replication, comprising virus uptake, transport, maturation, and extrusion. Virus uptake was observed within 10 hours of infection and occurred both as a result of fusion between virus and cell membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Some of the conclusions presented by other authors, although based on observations similar to ours, are, in our opinion, in disagreement with current views on cell pathobiology. Our results, when compared with much previous evidence [16,27,28,30,41,17,19], indicate that, with the sole exception of the formation of DB and black holes which seem a characteristic feature of H C M V infected cells, there are no m a r k e d differences in intracellular development between H C M V and other members of the Herpesviridae family. In fact, besides the intrinsic biological properties of each individual virus, this behavior seems to be due to the stereotyped response capabilities of cultured cells to injurious stimuli.…”
Section: Closing Commentscontrasting
confidence: 47%
See 1 more Smart Citation
“…Some of the conclusions presented by other authors, although based on observations similar to ours, are, in our opinion, in disagreement with current views on cell pathobiology. Our results, when compared with much previous evidence [16,27,28,30,41,17,19], indicate that, with the sole exception of the formation of DB and black holes which seem a characteristic feature of H C M V infected cells, there are no m a r k e d differences in intracellular development between H C M V and other members of the Herpesviridae family. In fact, besides the intrinsic biological properties of each individual virus, this behavior seems to be due to the stereotyped response capabilities of cultured cells to injurious stimuli.…”
Section: Closing Commentscontrasting
confidence: 47%
“…Epstein [9] and Siminoff [46] proposed that some naked cytoplasmic virions bud through the plasma membrane. It cannot be ruled out that some intracytoplasmic double enveloped capsids may derive their membranes from two sequential buddings through the nuclear and/or RER membranes as suggested by some authors [7,22,23,28,34,48]. In this case their exit through fusion with the plasma membrane appears unlikely because of the incoherence between the two types of membranes.…”
Section: Previous Hypothesesmentioning
confidence: 82%
“…10, routes N A 1 , B and C) is similar to larval oyster herpes-like virus replication. The replication of Gammaherpesvirinae (saimiriateles viruses) also involves intranuclear sacs with tubular elements and many dense fibrillar bodies (Tralka et al 1977, Luetzeler et al 19?9), but intranuclear tubular lamella-particle complexes (Tralka et al 1977), intranuclear electron-dense granules and occurrence of nucleocapsids within dense bodies (Luetzeler et al 1979) were not observed here. More importantly, the specificity of gammaherpesviruses for T and B lymphocytes (Roizman et al 1988) makes invertebrate infection unlikely.…”
Section: Discussionmentioning
confidence: 59%
“…The ultrastructure of H. saimiri and H. ateles in OMK cells has been described in several morphological studies (Morgan et al, 1970(Morgan et al, , 1973Heine et al, 1971;Heine and Ablashi, 1974;Friedman et al, 1976;Banfield et al, 1977;Tralka et al, 1977;Luetzeler et al, 1979). The morphogenesis follows the same general principles as that of other herpes-group viruses.…”
Section: E Morphogenesismentioning
confidence: 87%